Pengaruh Fitokimia Resveratrol terhadap Penurunan Kadar HbA1c pada Pasien Diabetes Melitus Tipe 2 (DMT2): Tinjauan Literatur - Riska Fitriani; Dominikus Raditya Atmaka (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Type 2 diabetes mellitus is a degenerative disease characterized by increased blood sugar levels due to insulin resistance. Many studies have examined the synergistic effect of nutraceutical supplementation to increase the effectiveness of drug therapy, one of which is resveratrol. However, studies that identify the effect of resveratrol on reducing HbA1c levels in patients with type 2 diabetes mellitus still have many inconsistencies in the reported results. The significance of these effects is based on the dose and timing of the particular intervention. Therefore, a literature review of several studies was carried out to assess the impact of resveratrol in treating type 2 diabetes mellitus through the HbA1c parameter and to explain the appropriate dose and duration of intervention. Articles included in the inclusion criteria are available in English and published within the last 10 years (2014-2024) in electronic databases such as PubMed-Medline, ScienceDirect, and SpringerLink. A literature review was conducted on experimental studies with type 2 diabetes patient subjects. The results of the literature review show that the recommended dose and duration that have the greatest significance in reducing HbA1c are at a dose of 200–500 mg/day for 6 months or >500 mg/day within 3 months. These results provide evidence that the adjusted dose and duration of resveratrol supplementation are very beneficial for the management of patients with type 2 diabetes mellitus.